PORTRAYAL OF A WITCH AS HEROINETHROUGH MALEFICENT CHARACTER IN MALEFICENT MOVIE (2014) - Farnush, Jemi; Sili, Surya; Ariani, Setya (Fakultas Ilmu Budaya Universitas Mulawarman, 2018)
ABSTRACT Maleficent movie (2014) a movie directed by Robert Stromberg and written by Linda Woolverton. This movie adapted from Sleeping Beauty animation version in 1959. Maleficent movie tells about the human Kingdom and the Moors Kingdom that have never be peace. This research focused on analyzing a portrayal of a witch as heroine through Maleficent character. The purposes of this research were to analyze kind of witch characteristics portrayed through Maleficent character in Maleficent movie, and to analyze Maleficent character portrayed as a heroine in Maleficent movie. This research was a qualitative research. This research used two theories. The first is witch theory by Julian Goodare and the second one is hero theory by Kendra Cherry. The results of the research showed, that Maleficent character in Maleficent movie (2014) evil and good side. There are four concepts of witch such as demonic, village, folkloric, and envisioned witch. Maleficent movie goes into the folkloric witch category. There are seventh elements of hero, which Maleficent character as a heroine in Maleficent movie. First, people who become heroes tend to be concerned with the well being of others. Second, heroes are good at seeing from the perspective of others. Third, heroes are competent and confident. Fourth, heroes have a strong moral compass. Fifth, heroes have right skills. Sixth, heroes persist even in the face of fear, and keep working on their goals. The second result showed that Maleficent character is a heroine. Keywords: hero, Maleficent, portrayal, witch ABSTRAK Film Maleficent (2014) adalah sebuah film yang disutradarai oleh Robert Stromberg dan ditulis oleh Linda Woolverton, film ini diadaptasi dari Sleeping Beauty versi animasi pada tahun 1959. Film Maleficent (2014) menceritakan tentang kerajaan Manusia dan kerajaan Moors yang tidak pernah berdamai. Penelitian ini fokus menganalisa penggambaran seorang wanita penyihir sebagai pahlawan melalui karakter Maleficent. Tujuan penelitian ini menganalisa jenis penggambaran karakteristik penyihir melalui karakter Maleficent di dalam film Maleficent. Penelitian ini merupakan penelirian kualitatif. Penelitian ini menggunaka dua teori. Yang pertama teori penyihir oleh Julian Goodare dan yang kedua teori pahlawan oleh Kendra Cheery. Hasil penelitian ini menunjukkan bahwa, yang pertama karakter Maleficent dalam film Maleficent (2014) sebagai seorang penyihir yang mempunyai sisi jahat dan baik. Ada empat konsep penyihir seperti demonic, village, folkloric, dan envisioned. Berdasarkan keempat konsep tersebut, film Maleficent masuk dalam kategori penyihir folkloric. Ada tujuh elemen kepahlawanan, dimana karakter Maleficent sebagai seorang pahlawan didalam film Maleficent (2014). Pertama, orang yang menjadi pahlawan cenderung memperhatikan kesejahteraan orang lain. Kedua, pahlawan pandai melihat sesuatu dari sudut pandang orang lain. Ketiga, pahlawan percaya diri. Keempat, pahlawan memiliki kompas moral yang kuat. Kelima, memiliki keterampilan. Keenam, pahlawan terus menghadapi ketakutan dan yang ketuju, pahlawan terus mengerjakan tujuan mereka, bahkan setelah menghadapi beberapa kemunduran. Kata kunci: pahlawan, Maleficent, penggambaran, penyihir